Effect of Non-phosphate Additive on Quality of Litopenaeus vannamei (Boone, 1931) - Chen, Yuansheng; Yang, Fujia; Guo, Yajing; Ni, Minglong; Wang, Mei; Yan, Fen; Fu, Caili (Fishery Technology, 2019)
Litopenaeus vannamei (Boone, 1931) was treated with non-phosphate additives viz., chitosan, collagen peptide and sodium chloride. Using single factor and orthogonal tests, the optimal proportions of chitosan, collagen peptide and sodium chloride were found to be 0.6, 2.0 and 0.5%, respectively. Besides, the effect of soaking time on the water retention capability indicated best results for 80 min. Under optimal conditions, the rate of increase in soaking weight, thawing loss, cooking loss, product yield, and the moisture content of the shrimp were observed as 9.80±1.14%, 6.09±2.87%, 32.96±2.31%, 73.65±3.56% and 71.38±0.52%, respectively. The water retention effect and texture of the samples treated with non-phosphate additive, commercial composite phosphate, and non-treated (control) were determined. The results revealed that nonphosphate additive could effectively improve the water-holding capacity of aquatic products, reduce the hardness, elasticity, adhesiveness and chewiness of shrimp significantly, and maintain the natural color and flavor.